Enhanced solubilization and extraction of hydrophobic bioactive compounds using water/ionic liquid mixtures. Issue 12 (10th May 2016) - Jin, Wenbin; Yang, Qiwei; Huang, Binbin; Bao, Zongbi; Su, Baogen; Ren, Qilong; Yang, Yiwen; Xing, Huabin
Abstract : The developed water/LCC-IL (long-chain carboxylate ionic liquid) mixtures exhibited extremely high solubilities for various hydrophobic bioactive compounds (HBCs) and excellent extraction efficiency for tocopherols. Abstract : Water is an ideal green solvent for the solubilization and separation of valued-added bioactive compounds in various chemical and biological processes, partly because water has a minimal impact on the environment and few safety issues. However, many bioactive compounds exhibit hydrophobic properties, which leads to their limited solubility in water and substantially hinders the development of green separation technologies using aqueous media. In this study, we construct a family of new water/ionic liquid (IL) mixtures with amphiphilic, anionic functional long-chain carboxylate ionic liquids (LCC-ILs) for the solubilization and extraction of hydrophobic bioactive compounds (HBCs). The LCC-ILs integrate both weak polarity and strong hydrogen-bonding basicity and, more importantly, have excellent lipophilicity while still being water-miscible; therefore, the water/LCC-IL mixtures exhibit extremely high solubilities for various HBCs. The quantitative solubilities (g g −1 ) of various HBCs, including tocopherol, perillyl alcohol, rutin, and ginkgolides, are as high as 1.46, 0.71, 0.39 and 0.43, respectively, at 35 °C in water/LCC-IL mixtures, which are the highest solubilities in aqueous solutions ever reported. The water/LCC-IL mixtures also exhibit excellent performance in the extraction of tocopherols from biomass with a yield 2 to 12 times that in common solvents. The microscopic solvent properties and dissolution mechanism were investigated. Nano-micelles were observed when tocopherol was dissolved in water/LCC-IL mixtures, and their dissolution ability was dependent on the alkyl chain length and the concentration of LCC-ILs. These results demonstrated the considerable potential of water/LCC-IL mixtures as promising green solvents for the solubilization and separation of HBCs.